Rhythmic gymnasts` injuries in a pediatric sports medicine clinic in the United States: a 10-year retrospective chart review - Gulati, R.; Rychlik, K.; Wild, J. T.; LaBella, C. R. (The Physician and Sportsmedicine, 2022)
Objectives Rhythmic gymnastics injuries have not been studied thoroughly especially in the United States. Existing research studies are predominantly from Europe or Canada or from more than 15 years ago. The purpose of our study was to provide an updated description of injury patterns among rhythmic gymnasts in the United States.